Intrathecal cytokine profile in neuropathy with anti‐neurofascin 155 antibody. Issue 11 (27th October 2019) - Ogata, Hidenori; Zhang, Xu; Yamasaki, Ryo; Fujii, Takayuki; Machida, Akira; Morimoto, Nobutoshi; Kaida, Kenichi; Masuda, Teruaki; Ando, Yukio; Kuwahara, Motoi; Kusunoki, Susumu; Nakamura, Yuri; et al.
Abstract: Objective: To characterize the CSF cytokine profile in chronic inflammatory demyelinating polyneuropathy (CIDP) patients with IgG4 anti‐neurofascin 155 (NF155) antibodies (NF155 + CIDP) or those lacking anti‐NF155 antibodies (NF155 − CIDP). Methods: Twenty‐eight CSF cytokines/chemokines/growth factors were measured by multiplexed fluorescent immunoassay in 35 patients with NF155 + CIDP, 36 with NF155 − CIDP, and 28 with non‐inflammatory neurological disease (NIND). Results: CSF CXCL8/IL‐8, IL‐13, TNF‐α, CCL11/eotaxin, CCL2/MCP‐1, and IFN‐γ were significantly higher, while IL‐1β, IL‐1ra, and G‐CSF were lower, in NF155 + CIDP than in NIND. Compared with NF155 − CIDP, CXCL8/IL‐8 and IL‐13 were significantly higher, and IL‐1β, IL‐1ra, and IL‐6 were lower, in NF155 + CIDP. CXCL8/IL‐8, IL‐13, CCL11/eotaxin, CXCL10/IP‐10, CCL3/MIP‐1α, CCL4/MIP‐1β, and TNF‐α levels were positively correlated with markedly elevated CSF protein, while IL‐13, CCL11/eotaxin, and IL‐17 levels were positively correlated with increased CSF cell counts. IL‐13, CXCL8/IL‐8, CCL4/MIP‐1β, CCL3/MIP‐1α, and CCL5/RANTES were decreased by combined immunotherapies in nine NF155 + CIDP patients examined longitudinally. By contrast, NF155 − CIDP had significantly increased IFN‐γ compared with NIND, and exhibited positive correlations of IFN‐γ, CXCL10/IP‐10, and CXCL8/IL‐8 with CSF protein. Canonical discriminant analysis of cytokines/chemokines revealed that NF155 + and NF155 − CIDP were separable, and that IL‐4, IL‐10, and IL‐13 were the three most significant discriminators. Interpretation: Intrathecal upregulation of type 2 helper T (Th2) cell cytokines is characteristic of IgG4 NF155 + CIDP, while type 1 helper T cell cytokines are increased in CIDP regardless of the presence or absence of anti‐NF155 antibodies, suggesting that overproduction of Th2 cell cytokines is unique to NF155 + CIDP.